Great Scientists - John Farndon, Alex Woolf, Anne Rooney & Liz Gogerly
Science is an ever-growing, ever-changing field of study. Every principle, every discovery is built on top of a previous discovery. Great scientists have studied life, the environment, and the physical world trying to learn more about why things are the way they are. Readers gain insight to some of the greatest scientific minds history has to offer, from Archimedes to Stephen Hawking.